The impacts of globalization on mental disorders : an effective solution from Islamic perspective - Abdul Razak, Abdul Latif (International Islamic University Malaysia, 2011)

(untitled)
Nowadays, the world in general is witnessing the frightening increase of psychological problems. This is due to the fast developmental changes brought by globalization and the marginalization of religion. Secular and irreligious psychological approaches which reject the spiritual aspects of man could not resolve the problems. Religion with its beliefs and practices guarantees the best and effective solutions to the problems. The challenge is how to apply those religious beliefs and practices in remedying those psychological problems. This requires right understanding of religious concepts and principles and the internalizations of these principles into daily life. This paper tries to embark upon discourse on the true understanding of the nature of man, his uniqueness compared to animal, and the meaning and purpose of his life. This true understanding of the nature of man leads to the understanding of the root causes of the problems and not the symptomatic ones. Consequently, the proper remedy can be given to cure these illnesses.